(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2021)
This work explores the possible uses of the term post-present. From a review of the meanings of postmetaphysics and postmodernity we find a closeness with the second. Regarding the type of experience derived from the post-present, we inquire how appropriate its relationship can be with the condition of being in Nietzschean transit and the fundamental state of mind of Heideggerian boredom. The moment acquires relevance compared to the temporal sequence.